Влияние различных физико-химических обработок на состояние поверхности порошков кубического нитрида бора - Новиков, Н.В.; Богатырева, Г.П.; Маринич, М.А.; Ищенко, Е.В.; Базалий, Г.А.; Козина, Г.К.; Гвяздовская, В.Л.; Зайцева, И.Н. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The physical-chemical properties of micro-, submicron сBN powders are conditioned by chemistry of their surface, i.e. by nature of substances adsorbed therein, functional groups. All this has an essential effect on sintering process. It has been established that on the surface of micro-, submicron сBN powders there are present physically and chemically adsorbed water vapours, oxygen in molecular and atomic form, nitrogen, ammonia, oxides and dioxides of nitrogen and boron, magnium oxide and boron hydride. This, in its turn, is the basis for creating the directed modification of powders supplied to the synthesis of polycrystalline materials and articles on their base.